Satellite Mega Constellations: Conflict between Freedom of Exploration and Unsustainable Outer Space Activities - Putro, Yaries Mahardika; Andriani, Popy; Salsabila, Gusti; Al Asyari, Haekal (Faculty of Law, Universitas Brawijaya, 2023)
In the era of space commercialization, the State is no longer the sole actor in international space activities; private companies such as SpaceX and OneWeb are now playing huge roles in these endeavors. The Mega constellation of satellites is devised by these private companies to provide low‐cost and low‐latency internet services to remote areas. This large-scale deployment is a network of a large number of satellites. Even though this connectivity venture is guaranteed under the freedom of exploration principle of the law of outer space, it is potentially hazardous in terms of problems connected with the accumulation of space debris and interference with astronomy research. Additionally, the legal vacuum concerning these issues is an area of great concern. This research has employed normative juridical research methods along with statutory and conceptual approaches. This study will examine the limits and scope of the principle of freedom of exploration and assess the urgency of ensuring the sustainability of mega constellation satellite projects. Through these examinations, the research aims to present the case for a robust space governance as a part of sustainable development practices.